Desarrollo participativo de un modelo de negocios para el fortalecimiento comercial y operacional de la organización comunitaria cosetur (2019)
Community based tourism, as a tourist management model (Maldonado, 2005), offers autonomy, the capacity of self-management and empowerment for the Social, Environmental, Ecological and Tourist Corporation - Cosetur, which is situated in the rural area of Buenaventura. However, the organization faces the challenge of strengthening its commercialization models that economically enhance its organizational and operational structure. Therefore, this project has the objective of proposing the participatory construction of a business model that helps facilitate the commercial and operational strengthening of the corporation. For this reason, this graduate work is based on a qualitative study that allows, from a descriptive approach, the identification of the conditions of supply and demand that determine the participatory development of a business model, to jointly and consciously construct the 9 modules that make up the Canvas Lean Model which was applied to the organization.